Physicochemical properties and growth kinetics of multilayer graphene by chemical vapor deposition for gas sensing application - Muslim, May Ali (2017)
This research has employed CVD to obtain high quality and large surface area MLG films on Co-Ni/Al2O3 substrate for gas sensing applications. The effect of process conditions on the yield of the MLG films grown on the Co-Ni/Al2O3 substrate was investigated using RSM. The employed parameters were reaction temperature (700-800°C), nominal catalyst (Co/Ni) composition (0.3-0.7), and ethanol flowrate (9-11ml/min) at a constant pressure. A total of 20 experimental runs were performed for the optimum growth condition of 77% yield of the MLG film. The optimal results show that the 800°C reaction temperature, a catalyst ratio of 0.3/0.7 with an ethanol flow rate of 11 ml/min were the best conditions for a scalable yield of large-area and high-quality MLG for gas sensing applications. The experimental test results show a correlation between the RSM predicted and experimental responses. The obtained MLG films was systematically characterized by using FESEM, EDX, HRTEM, RS, XRD, TGA and DTG, TEM analysis, FT-IR analysis and XPS analysis. All these characterizations confirm the excellent quality and number of layers of the MLG.